Osteoprotegerin Serum Level is Associated with Severity of Coronary Artery Calcification in Non Diabetic Centrally Obese Men - Trilis Yulianti; Antonia Anna Lukito; Andi Wijaya; Gatot Susilo Lawrence; Syakib Bakri (The Indonesian Biomedical Journal, 2012)
BACKGROUND: Osteoprotegerin (OPG) is produced by a variety of tissues including those of the cardiovascular system. Recent clinical studies have suggested a significant correlation between elevated OPG serum level and cardiovascular mortality. Since coronary artery calcification (CAC) is positively associated with cardiovascular disease (CVD) events, we carried out a study to investigate whether OPG serum level is associated with the severity of CAC in non diabetic centrally obese men.METHODS: A cross sectional study was done on seventy non diabetic centrally obese men. CAC score was determined by using dual source computed tomography (DSCT). OPG serum level was measured by enzyme-linked immunosorbent assay (ELISA) method. Statistical analysis was done with SPSS for windows ver 16. ANOVA was performed to analyze mean, maximum, minimum value, and standard deviation. Spearman correlation test was performed to determine the correlation between OPG serum level and CAC score. Significance value was defined as alpha level=0.05 based on two-tailed tests.RESULTS: OPG serum level was significantly correlated with CAC score. The severity of CAC increased with the increase of OPG level. Age was significantly correlated with OPG serum level and CAC score.CONCLUSIONS: Our data show that serum OPG level was associated with the severity of CAC, which highlights that OPG could be involved in the progression of CAC in non diabetic obese men.KEYWORDS: obesity, vascular calcification, osteoprotegerin, coronary artery calcification